Dead trees do tell tales: investigations into the role of fires on archaeological site location and recognition in the Piney Creek drainage of the greater Yellowstone ecosystem - Thompson, Abraham Kvale, author; Todd, Lawrence C., advisor; LaBelle, Jason M., committee member; Sibold, Jason S., committee member; Brown, Peter M., committee member; Coleman, Robert O., committee member (Colorado State University. Libraries, 2012)
The discovery and documentation of an archaeological site is dependent on three conditions. First, that people in the past left something behind; second, that those materials preserved; finally, that location is observed and documented by a researcher. Fires impact all three. Past fires would have interacted with available resources and caused changes to local and regional geomorphologic processes (conditions one and two). Perishable artifacts can be burned and destroyed in the heat of a fire. Even durable items such as projectile points can be modified by heat fracturing, spalling, and potlidding (condition two). Modern fires substantially increase the efficiency of the discovery and surface documentation of this material (condition three). During the summer of 2006, a large stand replacing fire, the Little Venus Fire (LVF), burned 14,164 ha acres of the Greybull River Drainage in Northwestern Wyoming. Under the burn were hundreds of archaeological sites that had been recorded before the LVF burned. After the fire, most of the reexamined sites revealed a wealth of new cultural material and added a previously undocumented Protohistoric record to this region. Fire scars on the whitebark pines in the Piney Creek Drainage in the Shoshone National Forest of Northwestern Wyoming show evidence of past fires. Crossdating these fire scars to tree ring samples from this drainage showed when this drainage burned in the past. Multiple fire scars dated to 1648. Temporally diagnostic artifacts including obsidian tri-notched projectile points, metal arrow points, and trade beads, as well as radiocarbon samples taken from processed bison bone, suggest that humans were present in this drainage in the years surrounding this fire. This research examines impacts of fires on both the resources available to prehistoric humans, and to research conducted by present-day archaeologists.
Keywords: dendrochronology; whitebark pine; landscape ecology; fire history; GRSLE; archaeology